STUDY REGARDING THE OPTIMAL DIMENSION OF THE S.C. AGROZOOTEHNICAL FARM S.A. WITH THE HELP OF STATISTICAL-MATHEMATICAL METHODS - Daniela SIMTION (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
An important problem, on which production and economic results depend for a long time, is the size of agricultural exploitations. The use of statistical methods, among which the one known as the "statistical method of studying the mass experience" or simply the "method of grouping", is the most widespread [10] in order to determine the optimum size of agricultural exploitations is based on the concept of statistical correlation, that can be attributed to the links between potential indicators (factorial or independent variables) and results and economic efficiency indicators (resultant or dependent variables) of an agricultural holding. The calculations show that the managers of the exploitations from the forth interval have made greater efforts to match the highest level of turnover and profit. How many? As far as the optimal number is concerned, it should be taken into account that the cost of production is more important to producers, as the sales price is formed under the impulse of the demand-supply ratio. In conclusion, the present study sets the optimal range related to the area of 3,801ha – 4,400ha and the optimal breeding females: 686 heads.